Effects of Family Violence on Psychopathology Symptoms in Children Previously Exposed to Maltreatment - Maikovich, Andrea Kohn (2008)
Although many studies suggest that family violence is associated with child psychopathology, multiple features of the home environment might account for this association, such as poverty and caregiver psychopathology. Studies are needed examining how change in psychopathology symptoms is affected by home violence, controlling for children's own developmental symptom histories and other predictors of psychopathology. This study used latent difference score structural equation modeling to test if witnessing home violence and/or experiencing harsh physical discipline predicted changes in psychopathology symptoms among 2,925 youth aged 5 – 16 years previously exposed to violence. Results demonstrated that harsh physical discipline predicted child-specific changes in externalizing symptoms, whereas witnessing violence predicted child-specific changes in internalizing symptoms across time. Implications for research and policy are discussed.